ANALISA KINERJA KEUANGAN PERUSAHAAN ASURANSI DI INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA MENGGUNAKAN EARLY WARNING SYSTEM PERIODE 2018-2021 - Diana, gesti; Yulefnita; Poppy Camenia Jamil; Sinta Yulyanti; Alfandi Yulio (Jurnal Ekonomi KIAT, 2024)
The purpose of this study was to determine the financial performance of insurance companies listed on the Indonesia Stock Exchange before and after the Covid-19 period 2018-2021 using the ratioEarly Warning system. This study uses the NAIC benchmark (National Assosiation of Insurence Commisioner). The population in this study consisted of 13 companies listed on the Indonesia Stock Exchange. The samples in this study were 5 companies listed on the Indonesia Stock Exchange according to the required criteria. The method used is quantitative analysis and descriptive analysis. The data used is the company's financial statements for the 2018-2019 period. The ratio that is outside the normal limits is the most common ratio underwriting and claim expense ratio. The ratio that many are within normal limits is the liquidity ratio. Based on the results of the ratios that have been calculated before and after covid, there is no significant difference in the financial performance of the companies studied. This can be seen in large part from the results of the 5 ratios during the 2018-2019 period which tend to be the same every year. Of the 5 companies studied, only the Bina Dana Arta Tbk Insurance company is included in the healthy category in terms of its financial performance.